A Class of Ruin Probability Model with Dependent Structure (Communications in Mathematical Research, 2021)
In this paper, we study a class of ruin problems, in which premiums andclaims are dependent. Under the assumption that premium income is a stochasticprocess, we raise the model that premiums and claims are dependent, give its numerical characteristics and the ruin probability of the individual risk model in the surplusprocess. In addition, we promote the number of insurance policies to a Poisson process with parameter $λ$, using martingale methods to obtain the upper bound of theultimate ruin probability.
Keywords: ruin probability; dependent structure; individual risk model; Poisson process.